Draft Eighth Five Year Plan 1990-95 and Draft Annual Plan 1991-92 (Volume I and II) Scheme-Wise Details Volume I (Sectors: 1-Agriculture to 29-Weights and Measures) Union Territory of Pondicherry - Planning Commission (Planning Commission, 1990)
The Union Territory of Pondicherry consists of four regions, namely, Pondicherry, Karaikal, Mahe and Yanam lying geographically isolated from one another Pondicherry region which is on the east coast, about 162 kms. South of Madras is the largest of these and consists of 12 scattered areas interspersed with enclaves of South Arcot District of Tamil Nadu Karaikal region is about 150 kms. south of Pondicherry and it is surrounded by Thanjavur District of Tamil Nadu.
Government of Pondicherry, Planning and Research Department